A Novel Seimatosporium and Other Sporocadaceae Species Associated with Grapevine Trunk Diseases in Cyprus - Kanetis, Loukas; Taliadoros, Demetris; Makris, Georgios; Christoforou, Michalis (My University, 2022)
Besides well-known grapevine trunk disease (GTD)-related pathogens, there is an increased interest in wood-colonizing fungi that infect grapevines. During 2017-2018, a survey was conducted in Cyprus and wood samples were collected from vines exhibiting typical GTD symptoms. Based on morphological and multilocus phylogenetic analyses (ITS, LSU, bt2, tef1-a), four species in the Sporocadaceae family were described and typified; two in the genus of Seimatosporium: Seim. cyprium sp. nov. and Seim. vitis-viniferae and two in Sporocadus: Spo. kurdistanicus and Spo. rosigena. The teleomorph of Seim. cyprium sp. nov. was also described. Pathogenicity trials with representative isolates of each species were performed on woody stems of two-year-old potted grapevines for 12 months under field conditions. All isolates were pathogenic, causing dark brown to black vascular discoloration, extending upward and downward from the inoculation point. Sporocadus isolates were significantly more aggressive than Seimatosporium with lesion lengths ranging from 9.24 to 6.90 and 4.13 to 4.00 cm, respectively. Successful re-isolations were also evident for all species and isolates. Seim. cyprium sp. nov. is a newly described species, while Spo. kurdistanicus and Spo. rosigena are reported for the first time in Europe on Vitis vinifera, suggesting the potential role of Sporocadaceae in the GTDs complex.
Keywords: Cyprus; Seimatosporium; Sporocadaceae; Sporocadus; Vitis vinifera; Grapevine trunk diseases